Metaphysical Experiences in Gražina Cieškaitė’s poetry - Peluritytė, Audinga (Literatūra, 2015)
This paper analyses and discusses the signs of metaphysical experience in the work of the contemporary Lithuanian poetess Gražina Cieškaitė. The paper was inspired by Vytautas Kavolis’ provoking thought that in Cieškaitė’s poetry attempt is made to analyse and criticise the key myths of Western civilisation, and female mythology, very old and going back to pre-civilisation conscience, is recreated from the shards of the broken myth of Western civilisation. In this paper, Cieškaitė’s work is analysed in several stages that are reflected in the headlines of the sections. Recognisable are the landmarks of metaphysical thinking, mythical personages and plots; discussed are the outcomes of the interaction of eclectic metaphysical and mythical thinking; finally, an attempt is made at recognising the central idea of this metaphysical lyric and at reconstructing the version of myth so closely linked with this idea. All parts of the paper are concerned with the issue of poetic language, and the key features of Cieškaitė’s poetics are recorded. The paper asserts that in Cieškaitė’s work it is really possible to restore an extremely old version of female mythology, which is embodied in the figure of the goddess Aphrodite that had acquired Promethean creative powers. Yet here metaphysical experiences can hardly be generalised as one comprehensive metaphysical theory. In Cieškaitė’s work, metaphysical thinking based on language and logic frequently yields ground to spontaneous mystical experiences, which are not controlled by either logic or language.